A serological survey for Bhanja and tick-borne encephalitis viruses in sheep of eastern Slovakia - Hubálek, Z; Mitterpák, J; Prokopic, J; Juricová, Z; Kilík, J (Folia parasitologica, 1985)
755 sheep from 41 farms in the districts of Trebisov, Michalovce, Humenné and Roznava in the East Slovakian region were investigated on the presence of antibodies to Bhanja (neutralization test) and tick-borne encephalitis (haemagglutination-inhibition test) viruses. In respective districts 2.2%, 0.4%, 1.7% and 26.7% of animals (total 5.3%) were found to be positive on Bhanja virus, 4.4%, 1.5%, 1.7% and 5.0% (total 2.6%) on tick-borne encephalitis (TBE) virus. The considerable infection rate in sheep with Bhanja virus in the district of Roznava (mean 26.7%-on one farm as high as 63.9% serologically positive animals) can be explained by the local occurrence of the tick Haemaphysalis punctata, the main vector of this virus in Europe. The serologic screening conducted indicates a low activity of natural foci of TBE in eastern Slovakia today, and confirms the existence of a natural focus of infection with Bhanja virus in the district of Roznava. Recent circulation of Bhanja virus is indicated by antibodies detected in several one-year-old sheep.
Keywords: viry klíšťové encefalitidy; Seasons; infekce viry z čeledi Bunyaviridae; Ticks; nemoci ovcí; ovce; Czechoslovakia; Encephalitis, Tick-Borne; Československo; Antibodies, Viral; Encephalitis Viruses, Tick-Borne; Bunyaviridae; Hemagglutination Inhibition Tests; Sheep Diseases; testy inhibice hemaglutinace; klíšťová encefalitida; zvířata; klíšťata; Bunyaviridae Infections; protilátky virové; neutralizační testy; Sheep; roční období; Neutralization Tests; Animals